Implikasi Hukum dan Etika dalam Kasus Pelanggaran Rahasia Dagang : Studi Kasus PT Chiyoda Kogyo Indonesia - Moch. Virgi Arivandi; Nadia Dwi Ramadani; Nur Rohma; Rafela Yumaning Putri; Emma Yunika Puspasari (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
The case of alleged violation of company secrets of PT Chiyoda Kogyo Indonesia, involving PT Maruka Indonesia, Hiroo Yoshida, and PT Unique Solutions Indonesia, who allegedly conspired to obtain confidential information in accordance with Article 23 of Law No. 5 Year 1999. This alleged violation caused potential financial losses of up to Rp 63 billion for PT Chiyoda Kogyo Indonesia and threatened its reputation. The protection of company secrets is crucial in maintaining a competitive advantage in an innovation-laden industry. This research explores the legal aspects and business impact of leaking sensitive information, focusing on the Trade Secrets Act (UURD) and the Antimonopoly Act, and its implications for fair business competition. The analysis is conducted through a normative legal approach, assessing the relevance of contract and property rights theories in the context of trade secret protection. In addition, it is recommended that companies implement stricter information security strategies, such as Non-Disclosure Agreement (NDA) contracts and confidentiality agreement renewals, to prevent future leaks.